(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article emphasizes that the in-depth study of words and their logical possibilities is a key factor in determining our future, under the conditions of national revival in the new Uzbekistan’s development and the effectiveness of scientific research activities related to our language. From a linguistic perspective, this study of speech units provides a detailed analysis of the semantic characteristics of words, the scope of semantic fields, the onomastic status, as well as the denotative and connotative functions in expressing meanings or concepts, along with the significant and structural forms of these functions.